Benchmarking as a Marketing Strategy Promotion for Increasing Tourism: Case Study of SMEs in Kediri City Square - Iva Khoiril Mala; Puji Handayati; Arief Noviarakhman Zagladi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses strategies to increase the number of visitors to the SME square in Kediri through benchmarking and collaboration between related parties. Kediri Square has undergone significant revitalization and facial changes to increase its appeal. Apart from being a tourist spot, Kediri Square is also used as an educational place. This research also highlights the importance of internal marketing strategies effective promotion, integration of local culture, and cooperation with related parties. The research method used is qualitative with a case study approach to alun-alun SMEs Kediri city with observation and interviews. The research results show that developing attractive facilities, effective promotions, increasing security and comfort, and collaborating with related parties can increase the number of visitors. In addition, combining educational activities and promotion of local culture can also be an effective strategy. In its conclusion, this research emphasizes the importance of cooperation between local government, tourism actors and local communities in increasing the number of visitors to Kediri Square.